Evaluation of the synergistic effects of curcumin-resveratrol co-loaded biogenic silica on colorectal cancer cells - Ochoa-Sanchez, Adriana; Sahare, Padmavati; Pathak, Surajit; Banerjee, Antara; Estevez, Miriam; Duttaroy, Asim K.; Luna-Bárcenas, Gabriel; Paul, Sujay (Frontiers in Pharmacology, 2024)
Colorectal cancer (CRC) remains a significant global health concern, being the third most diagnosed cancer in men and the second most diagnosed cancer in women, with alarming mortality rates. Natural phytochemicals have gained prominence among various therapeutic avenues explored due to their diverse biological properties. Curcumin, extracted from turmeric, and resveratrol, a polyphenol found in several plants, have exhibited remarkable anticancer activities. However, their limited solubility and bioavailability hinder their therapeutic efficacy. To enhance the bioavailability of these compounds, nanomaterials work as effective carriers with biogenic silica (BS) attracting major attention owing to their exceptional biocompatibility and high specific surface area. In this study, we developed Curcumin-resveratrol-loaded BS (Cur-Res-BS) and investigated their effects on colorectal cancer cell lines (HCT-116 and Caco-2). Our results demonstrated significant concentration-dependent inhibition of cell viability in HCT-116 cells and revealed a complex interplay of crucial proto-onco or tumor suppressor genes, such as TP53, Bax, Wnt-1, and CTNNB1, which are commonly dysregulated in colorectal cancer. Notably, Cur-Res-BS exhibited a synergistic impact on key signaling pathways related to colorectal carcinogenesis. While these findings are promising, further investigations are essential to comprehensively understand the mechanisms and optimize the therapeutic strategy. Moreover, rigorous safety assessments and in vitro studies mimicking the in vivo environment are imperative before advancing to in vivo experiments, ensuring the potential of Cur-Res-BS as an efficient treatment for CRC.